New Challenges in Accounting, Auditing and Taxation – Report on the VII János Bosnyák International Commemorative Conference - Gulyás, Éva; Martin, Kíra (Public Finance Quarterly, 2025)
On 14 February 2024, the VII János Bosnyák1 International Commemorative Conference was held at the Corvinus University of Budapest. The event traditionally provides an opportunity for academics and PhD students from higher education institutions to present the results of their research, to discuss the conclusions in the context of practical experience, and to jointly reflect on the challenges and possible solutions for the problems identified. Following is a summary of the key ideas and messages from a selection of the speakers at the conference.